Investigating the Impact of the Tier 4 Policy on International Students at Private Colleges in the UK - Mughal, Abdul Waheed (Journal of International Students, 2016)
In 2009, the United Kingdom government introduced the Tier 4 (general) student visa policy for foreign students, out of European Economic Area and Switzerland, aged 16 or over. According to this policy, any institution recruiting international students must be a highly trusted sponsor - a status determined by the UK Border Agency. Further, right to work during study was totally denied for the non-EEA students of private colleges in 2011. This study explores the experiences of non-EEA students of private colleges in the wake of such changes. The research objectives were met through conducting individual interviews with 45 students from ten different countries studying at two private colleges in London. The results showed that the Tier 4 policy had negatively impacted the ambitions of studying in the UK at private colleges. About 97% of the interviewees said that they would not recommend private colleges to similar prospective students...